Bir Halk Sağlığı Müdürlüğü’nde çalışanların organik gıda tüketimi ve sağlık algıları ilişkisinin incelenmesi - Atasağun, Ayşe Özgül (My University, 2022)
Giriş ve Amaç: Organik tarım, sağlığa olumlu katkı sunması, çevre sağlığı ve hayvan refahını gözetmesi ve gelecek nesiller için önem arz etmektedir. Bu çalışma, bireylerin organik gıda tüketimlerini ve organik gıda hakkındaki bilgi, tutum ve davranışları ile sağlık algıları ilişkisini belirlemeyi amaçlamaktadır. Gereç ve Yöntem: Isparta ili Halk Sağlığı Müdürlüğü’nde yürütülen araştırma kesitsel tipte planlanmıştır ve tüm çalışanlar (n=290) araştırma kapsamına alınmıştır. Veriler yüzyüze anket yoluyla toplanmıştır. Araştırmada 27 sorudan oluşan anket formu, 18 maddeden oluşan Organik Gıda Tüketim Ölçeği ile 15 maddeden oluşan Sağlık Algısı Ölçeği kullanılmıştır. Kategorik değişkenler; Ki-kare, Fisher, ölçümsel değişkenler; Student’s T, One-way ANOVA, Pearson Correlation testleri ile değerlendirilmiştir. Bulgular: Araştırmaya katılım oranı %95.17 olarak tespit edilmiştir (n=276). Araştırmaya katılanların %68,8’i kadındır (n=190). Araştırmaya katılanların yaş ortalaması 43,24±7,95 yıldır. Katılımcıların Sağlık Algısı Ölçeği puan ortalaması 41,88±6,8, Organik Gıda Tüketim Ölçeği puan ortalaması ise 58,71±14,89 olarak tespit edilmiştir. Katılımcıların sağlık algısı ile organik gıda tüketimi arasında pozitif yönde orta düzeyde anlamlı bir ilişki saptanmıştır (r =0.273, p<0.001). Sonuç: Sağlık algısı ile organik gıda tüketimi arasında anlamlı bir ilişkinin olması sağlığını önemseyen bireylerin güvenilir ve sağlıklı gıda arayışlarının bir sonucu olabilir. Üreticileri teşvik etmek ve tüketicileri bilinçlendirme çalışmaları toplumun sağlık algısı düzeyini artıracaktır bu da daha sağlıklı bir toplumu oluşturacak olup toplumun sağlık harcamalarını azaltacak ve ekonomiye katkı sağlayacaktır.

Introduction and Aim: Organic agriculture is essential for consumers because it contributes positively to health, protects environmental health and animal welfare, and for future generations. This study aims to determine the organic food consumption of individuals and to determine the relationship between their knowledge, attitudes, behaviours about organic food and their health perceptions. Materials and Methods: The research which was carried out in the Isparta Provincial Directorate of Public Health was planned in cross-sectional type and all employees (n=290) were included in the study. Data was collected through face-to-face survey. In the research, a questionnaire consisting of 27 questions, the Organic Food Consumption Scale consisting of 18 items and the Health Perception Scale consisting of 15 items were used. Categorical variables were evaluated with Chi-square, Fisher and measurement variables were evaluated with Student's T, One-way ANOVA, Pearson Correlation tests. Results: The rate of participation in the study was determined as 95.17% (n=276). 68.8% of the participants in the study were women (n=190). The age average of the participants in the study was 43.24±7.95 years. The participants' Health Perception Scale average score was 41.88±6.8, and the Organic Food Consumption Scale mean score was 58.71±14.89. A moderately significant positive correlation was found between the participants' health perception and organic food consumption (r =0.273, p<0.001). Conclusion: The fact that there is a significant relationship between health perception and organic food consumption may be a result of individuals’, who care about their health, search for reliable and healthy food. Encouraging the producers and raising awareness of the consumers will increase the level of health perception of the society, which will create a healthier society, reduce the health expenditures of the society and contribute to the economy.
Examination of the relationship of organic food consumption and health perceptions of employees in a public health directorate
Keywords: Beslenme; Cooking (Natural foods); Doğal besinler; food; gıda Organic food; health; Health aspects; health perception; Mutfak (Doğal besinler); Natural foods; Nutrition; organic agriculture; Organik gıda; organik tarım; sağlık; sağlık algısı; Sağlık yönleri